Transumano, um conceito sobre a produção de corpos e subjetividades na era digital - Fusaro, Luana Garcia Feldens (2024)
This thesis proposes a new concept for the idea of “transhuman”. This is an ontological discussion related to recent technologies, especially bioscience and digital systems. The transhuman is approached through the processes and experiments that these technologies provoke in social and political dynamics, crossing ways of life. The aim is to show how these technologies operate as social and power devices, producing subjectivities and new existential territories. Thus, the transhuman is treated not as a reference to the creation of a new human being, but as a conceptual tool capable of interpreting certain processes of the human experience. The approach of this research is expanded on literary, cinematic, factual, theoretical and philosophical references, with which we seek to create intersections, composing a network of meanings and signifiers that support the proposed concept. This conceptual network is formed to discuss respect for one's own understanding of what it means to be human; about control and power dynamics; and about ethical issues involving disputes under the domain of biological condition. The aim is, therefore, to promote both a conceptual elaboration on the transhuman, as well as critical thinking on how these processes cross ways of life